PEMBELAJARAN ESTETIKA RESEPSI SASTRA LAHAN BASAH SEBAGAI MODEL PEMBELAJARAN BERDIFERENSIASI (TEACHING AND LEARNING THE RECEPTION AESTHETIC OF WETLAND LITERATURE AS A DIFFERENTIATED LEARNING MODEL) - Hermawan, Sainul; Effendi, Rustam; Yasin, Moh Fatah; Sabhan, Sabhan; Alfianti, Dewi; Syaifullah, Syaifullah; Fitriani, Fitriani; Aryadi, Aryadi (Universitas Lambung Mangkurat, 2024)
AbstractTeaching and Learning the Reception Aesthetic of Wetland Literature as A Differentiated Learning Model. This study aims to examine the aesthetics of students' reception of short stories set in wetlands. Achieving this goal is important to show that learning aesthetics of reception can be used as one of the differentiated learning models that is in line with one of the missions of the national curriculum. Wetland literary texts by South Kalimantan authors and students are the main data sources for this study. The data for this study are students' aesthetic responses to literary texts. These responses are studied phenomenologically to reveal students' understanding of wetland environmental issues in the text. This study will examine the aesthetic responses of 25-30 students at SMA Negeri 1 Batu Ampar in Tanah Laut Regency, South Kalimantan. The location of this study was chosen because this school has implemented the Merdeka Curriculum and research related to this national curriculum is still rarely conducted in that place. The responses of the data sources were analyzed to answer the following research problems: How do students respond to various types of wetland literary works presented to them? How does the learning model involve students in learning and how does this involvement impact their understanding of intrinsic elements in relation to understanding social and cultural backgrounds? What are the advantages and disadvantages of this learning model? The study found that contextual learning in the sense of learning that uses teaching materials that are close to the students' culture has the potential to increase student involvement in learning. This learning model succeeded in creating an in-depth discussion about the intrinsic elements of short stories. The elements of the short story were not only identified in terms of their types but also critically thought about the process of their creation. Second, this learning model made students aware of the differences in interpretation when the short story was read by different readers. In other words, this learning model not only fosters critical thinking but also teaches about the importance of democracy and empathy.Keywords: reception aesthetics, wetland literature, differentiated learning AbstrakPembelajaran Estetika Resepsi Sastra Lahan Basah sebagai Model Pembelajaran Berdiferensiasi. Penelitian ini bertujuan untuk mengkaji estetika resepsi siswa terhadap cerita pendek berlatar lahan basah. Pencapaian tujuan tersebut penting untuk menunjukkan bahwa pembelajaran estetika resepsi dapat dijadikan salah satu model pembelajaran berdiferensiasi yang selaras dengan salah satu misi kurikulum nasional. Teks sastra lahan basah karya penulis Kalimantan Selatan dan siswa menjadi sumber data utama penelitian ini. Data penelitian ini berupa respons estetik siswa terhadap teks sastra. Respons tersebut dikaji secara fenomenologis untuk mengungkap pemahaman siswa terkait dengan isu lingkungan lahan basah yang ada dalam teks. Penelitian ini akan mengkaji respons estetik 25-30 siswa di SMA Negeri 1 Batu Ampar di Kabupaten Tanah Laut, Kalimantan Selatan. Lokasi penelitian ini dipilih karena sekolah ini telah menerapkan Kurikulum Merdeka dan penelitian yang terkait dengan kurikulum nasional ini masih jarang dilakukan di tempat tersebut. Respons sumber data dianalisis untuk menjawab masalah penelitian sebagai berikut: Bagaimana siswa merespons berbagai jenis karya sastra lahan basah yang dipresentasikan kepada mereka? Bagaimana model pembelajaran melibatkan siswa dalam pembelajaran dan bagaimana dampak pelibatan tersebut bagi pemahaman mereka tentang unsur intrinsik dalam kaitannya dengan pemahaman latar sosial dan budaya? Bagaimana kelebihan dan kekurangan model pembelajaran ini? Penelitian menemukan bahwa pembelajaran yang kontekstual dalam arti pembelajaran yang menggunakan bahan ajar yang dekat dengan budaya siswa berpotensi meningkatkan keterlibatan siswa dalam pembelajaran. Model pembelajaran ini berhasil membuat diskusi mendalam mengenai unsur intrinsik cerpen. Unsur-unsur cerpen bukan hanya diidentifikasi jenis-jenisnya tetapi juga dipikirkan secara kritis proses penciptaannya. Kedua, model pembelajaran ini menyadarkan siswa tentang perbedaan tafsir ketika cerpen dibaca oleh pembaca yang berbeda. Dengan kata lain, model pembelajaran ini bukan hanya menumbuhkan pemikiran kritis tetapi juga mengajarkan tentang pentingnya demokrasi dan empati.Kata-kata kunci: estetika resepsi, sastra lahan basah, pembelajaran berdiferensiasi